2015
DOI: 10.3233/jbr-150098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of site and genotype on strawberry fruits quality traits and bioactive compounds

Abstract: Site effects on the main active and putative health-promoting compounds of strawberry were investigated using 5 strawberry genotypes. The plants were grown at three locations in Italy (Verona and Cesena in the North and Scanzano Jonico in the South) of differing latitude, environmental conditions (temperature) and crop management practices (planting date, plant type, harvest duration, yield per plant and per day) influencing fruits quality traits. At each site, fruits for analysis were picked at mid harvest (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 33 publications
8
20
1
Order By: Relevance
“…Strawberry fruit is well known as an excellent source of different antioxidants and secondary metabolites such as ascorbic acid and phenolic compounds [16]. Other authors have found that genotype and cultivation technique have significant effects on the content of the secondary metabolites in strawberry fruits [38][39][40]. Our results showed that improvement in fruit ascorbic acid, anthocyanins, polyphenol contents, and antioxidant capacity can be accomplished through the combined use of soil solarization and CaCN 2 treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Strawberry fruit is well known as an excellent source of different antioxidants and secondary metabolites such as ascorbic acid and phenolic compounds [16]. Other authors have found that genotype and cultivation technique have significant effects on the content of the secondary metabolites in strawberry fruits [38][39][40]. Our results showed that improvement in fruit ascorbic acid, anthocyanins, polyphenol contents, and antioxidant capacity can be accomplished through the combined use of soil solarization and CaCN 2 treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Polyphenolic metabolites are thought to accumulate in plants as a consequence of stress or pathogenic infiltration [9]. Modern agriculture limits these stresses; Joven et al suggested that in a western diet it would be difficult to consume enough polyphenols from fruit and vegetables to influence health as a result of reduced polyphenolic profiles due to modern agricultural practices [10,11]. Furthermore, the mean consumption of fruit and vegetable servings per person in the US is half of the recommended portions at 1.5-2 cups and 2-3 cups, respectively, per day [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is a relationship between temperature and genotype, and the increase in the thermal amplitude between day and night can affect the colour of the fruits (Šamec et al, 2016). In addition, the value of C* can be influenced by the location where the fruits are produced (Cocco et al, 2015). For example, when the cultivar Korona was cultivated in areas farther south relative to the Northern Hemisphere, higher values of C* were observed compared with those grown farther north, suggesting a positive effect of low temperatures on colour saturation (Krüger et al, 2012).…”
Section: Substrates Camarosa Albionmentioning
confidence: 99%
“…In the state of Rio Grande do Sul, there are regions approximately 900 m above sea level with low summer temperatures, which would provide suitable climatic conditions for the production of strawberry transplants (Wrege et al, 2007). When strawberry transplants are started in cooler locations, they can achieve relatively higher rates of productivity and fruit quality than can transplants started in warmer locations; the environment where a transplant was produced has a direct influence on cultivation and final production (Cocco et al, 2015).…”
Section: Introductionmentioning
confidence: 99%